1991
DOI: 10.1042/bj2750623
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and immunological properties of selenium-containing glutathione peroxidase induced by selenite in Chlamydomonas reinhardtii

Abstract: The selenite-induced glutathione peroxidase in Chlamydomonas reinhardtii has been purified about 323-fold with a 10% yield, as judged by PAGE. The native enzyme had an Mr of 67,000 and was composed of four identical subunits of Mr 17,000. Glutathione was the only electron donor, giving a specific activity of 193.6 mumol/min per mg of protein. L-Ascorbate, NADH, NADPH, pyrogallol, guaiacol and o-dianisidine did not donate electrons to the enzyme. In addition to H2O2, organic hydroperoxides were reduced by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 34 publications
0
28
1
Order By: Relevance
“…Thus, the results presented in this study indicate that CrGPX is different from the one characterized by Shigeoka et al (22). We have found a protein of a different subunit M r , the corresponding gene sequence does not confirm a tetrameric structure, and our GPX did not cross-react with bovine erythrocyte GPX antibodies, kindly provided to us by Dr. M. Lecomte (data not shown).…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…Thus, the results presented in this study indicate that CrGPX is different from the one characterized by Shigeoka et al (22). We have found a protein of a different subunit M r , the corresponding gene sequence does not confirm a tetrameric structure, and our GPX did not cross-react with bovine erythrocyte GPX antibodies, kindly provided to us by Dr. M. Lecomte (data not shown).…”
Section: Discussioncontrasting
confidence: 65%
“…Two other reports showed that, in Euglena gracilis, a purified selenium-independent GPX-like protein resembled classical GPX in its activity and structure (46) and, in C. reinhardtii, a selenium-dependent GPX was found to be a tetramer composed of identical subunits (22).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Early studies had indicated that addition of sodium selenite to Chlamydomonas cultures led to a strong increase in GPX activity in total soluble extracts (Yokota et al 1988). Purification of the corresponding protein revealed that the enzyme was associated with selenium and exhibited biochemical properties comparable to mammalian selenoGPXs (Shigeoka et al 1991). Although these studies suggested the existence of selenoGPX in Chlamydomonas, no DNA or protein sequence was determined.…”
Section: The Glutathione Peroxidase Familymentioning
confidence: 99%